Potentially malignant disorders of the oral cavity: Current practice and future directions in the clinic and laboratory. Issue 3 (11th February 2014) - Dionne, Kalen R.; Warnakulasuriya, Saman; Binti Zain, Rosnah; Cheong, Sok Ching
<x xml:space="preserve">Abstract</x> Despite commendable progress in the prevention, detection, and treatment of a wide variety of solid tumor types, oral squamous cell carcinoma (OSCC) remains a significant health burden across the globe. OSCC carcinogenesis involves accumulation of genetic alterations that coincide with the multistep malignant transformation of normal oral epithelium. OSCC is often first diagnosed at late stages of the disease (advanced regional disease and/or metastasis). Delayed diagnosis precludes successful treatment and favorable outcomes. In clinical practice, opportunities exist to identify patients with oral potentially malignant disorders (OPMDs), which precede the development of cancer. This review addresses the current status of laboratory and clinical research on OPMDs, with emphasis on leukoplakia and erythroplakia. OSF is also presented, though there is a paucity of published studies on this disorder. We focus on findings that could translate into earlier diagnosis and more efficacious treatment of those lesions with significant malignant potential. We explore how markers of OPMD malignant transformation might be implemented into current diagnostic practice to help clinicians objectively stratify patients into treatment/follow‐up groups according to relative risk. We provide an overview of recently concluded and ongoing OPMD chemoprevention trials. We describe laboratory OPMD models that can be used to not only to reveal the genetic and molecular intricacies of oral cancer but also to develop novel screening methods and therapeutic approaches. Finally, we call for targeted screening programs of at‐risk populations in order to facilitate diagnosis and treatment of OPMD and early OSCC.